Structural Mechanics : Loads, Analysis, Materials and Design of Structural Elements /: Loads, Analysis, Materials and Design of Structural Elements. (2010) - Durka, Frank; Al Nageim, Hassan; Morgan, W; Williams, D
No abstract available